PENERAPAN METODE FULL COSTING UNTUK MENENTUKAN HARGA POKOK PRODUKSI ( STUDI KASUS PETERNAKAN BEBEK) DI SIDOARJO - Enny Istanti (AKUNTANSI 45, 2022)
The progress of the business world is currently moving rapidly regardless of the size and development of the industrial sector which also plays an important role in the economic sector. The purposes of this study are 1. To find out how the implementation of the Full Costing method of duck farmers in determining the cost of production, 2. To find out the amount of the cost of production in the duck farming business and 3. To find out whether the calculation of the cost of production based on the full costing method has an effect on increase in profit. A qualitative approach is a research method that produces descriptive data in written or oral form from people and observable behaviors. The cost of egg production per kilogram obtained using the full costing method in the 2020-2021 period is Rp. 16,177.77/kg. The method of calculating the cost of production using the full costing method would be better used by duck farmers, if you want to get a more accurate profit based on accounting calculations, because this method has included all costs, including depreciation of equipment and depreciation of cages.